2011
DOI: 10.1063/1.3655467
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic properties of alkali atoms embedded in Ar matrix

Abstract: We present a theoretical investigation of visible absorption and related luminescence of alkali atoms (Li, Na, and K) embedded in Ar matrix. We used a model based on core polarization pseudopotentials, which allows us to determine accurately the gas-to-matrix shifts of various trapping sites. The remarkable agreement between our calculated results and the experimental spectra recorded by several authors allows us to establish a clear assignment of the observed spectra, which are made of contributions from crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 36 publications
3
45
0
Order By: Relevance
“…Absorption triplets could be assigned to specific matrix sites, but emission spectra had poor agreement with experiment. Using a model based on core polarization pseudopotentials, a much better match to experimental emission spectra was obtained for Na in SAr, and various peaks in observed spectra could be assigned to four distinct matrix sites [24]. Recently, the molecular pair potentials of various states of BaXe and BaXe + have been calculated [27].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Absorption triplets could be assigned to specific matrix sites, but emission spectra had poor agreement with experiment. Using a model based on core polarization pseudopotentials, a much better match to experimental emission spectra was obtained for Na in SAr, and various peaks in observed spectra could be assigned to four distinct matrix sites [24]. Recently, the molecular pair potentials of various states of BaXe and BaXe + have been calculated [27].…”
Section: Discussionmentioning
confidence: 97%
“…Such large shifts do occur for alkali atoms in noble gas matrices. For example, calculations have shown that the "blue" and "violet" triplets of Li, Na and K atoms in SAr matrices are due to atoms in sites with one and four neighboring vacancies, in which neighbor interactions with the alkali atom are relatively strong [24]. Further experimental and theoretical work is needed to assign these new blue transitions.…”
Section: Discussionmentioning
confidence: 99%
“…Both methods are size consistent, which is important when the number of correlated electrons increases. The computation of the B 2 + PEC was completed by model calculations similar to those used for Ne and Ar 5,[21][22][23] and adapted for Kr. Though not overwhelming, the relativistic effects are not completely negligible for atoms like Kr and Xe.…”
Section: Methodsmentioning
confidence: 99%
“…This relative simplicity is particularly convenient to investigate more complex situations when the M is coupled to additional rare gas atoms at the surface of RG clusters, or trapped in RG matrices, and to unravel the fine details of the guest-hosts interaction. Models based either on diatomics-inmolecules [1][2][3] or on core polarization potential (CPP) 4,5 have been used to investigate these more complex situations. In both cases, reliable potential energy curves (PEC) for dimers are necessary to parameterize or to assess the quality of the models.…”
Section: Introductionmentioning
confidence: 99%
“…The recent theoretical study by Gervais and co-workers [16] on the alkali metal atom series (M = Li, Na and K) isolated in solid argon has provided considerable insight into the isolation of range of guest atoms in a given matrix system. On a related subject, Fajardo has used Monte Carlo techniques on the Li/Ne [17] system to investigate the occupancy of this metal atom in a solid neon host.…”
Section: Introductionmentioning
confidence: 99%